Extrapolation of enalapril efficacy from adults to children using pharmacokinetic/pharmacodynamic modelling. (10th August 2015) - Kechagia, Irene‐Ariadne; Kalantzi, Lida; Dokoumetzidis, Aristides
Abstract Objectives To extrapolate enalapril efficacy to children 0–6 years old, a pharmacokinetic/pharmacodynamic (PKPD) model was built using literature data, with blood pressure as the PD endpoint. Methods A PK model of enalapril was developed from literature paediatric data up to 16 years old. A PD model of enalapril was fitted to adult literature response vs time data with various doses. The final PKPD model was validated with literature paediatric efficacy observations (diastolic blood pressure (DBP) drop after 2 weeks of treatment) in children of age 6 years and higher. The model was used to predict enalapril efficacy for ages 0–6 years. Key findings A two‐compartment PK model was chosen with weight, reflecting indirectly age as a covariate on clearance and central volume. An indirect link PD model was chosen to describe drug effect. External validation of the model's capability to predict efficacy in children was successful. Enalapril efficacy was extrapolated to ages 1–11 months and 1–6 years finding the mean DBP drop 11.2 and 11.79 mmHg, respectively. Conclusions Mathematical modelling was used to extrapolate enalapril efficacy to young children to support a paediatric investigation plan targeting a paediatric‐use marketing authorization application.